Influence of different phosphorus levels on growth, productivity and profitability of mungbean in semi-arid regions of South Afghanistan - Jahish, Fraidoon; Bana, R.S.; Choudhary, Anil K. (Annals of Agricultural Research, 2018)
An experiment was conducted at Afghanistan National Agricultural Science and Technology University (ANASTU), Kandahar (Afghanistan) during March-June 2015 to study the effect of seven phosphorus levels (0, 20, 40, 60, 80, 100 and 120 kg P2O5 ha–1) on the growth behaviour and productivity of mungbean (Vigna radiata L. Wilczek). Phosphorus levels, with a few expectations, remarkably improved the growth attributes and productivity of mungbean. At harvest stage of mungbean, maximum plant height (51.3 cm), number of branches plant–1 (5.5), dry matter accumulation plant–1 (31.6 g), root dry weight plant–1 (1.1 g), were recorded with 60 kg P2O5 ha–1 treatment. Leaf area index (3.84 at 60 DAS) and crop growth rate (0.31 g cm2 day–1 at 30 DAS-60 DAS) were also highest when phosphorus was applied to the crop @ 60 kg P2O5 ha–1. In general, maximum mungbean grain yield (1.61 t ha–1), net returns (94,700 AF ha–1), production efficiency (17.9 kg ha-1 day–1) and monetary efficiency (1,05 AF ha–1 day–1) were recorded with 60 kg P2O5 ha–1. However, phosphorus fertilization did not affect harvest index significantly.